The Influence of Leadership Style, Work Motivation, and Career Development on Turnover Intention - Trizia Andini; Didin Hikmah Perkasa (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
This study is to determine the influence of leadership style, motivation, and career development on turnover intention of PT. X. The object of this research is the employees of PT X. Quantitative research with a cross-sectional approach. Data collection was carried out in 2019 at PT X.A statistical analysis of the data used was a multiple linear regression test. The sampling technique used was purposive sampling. The sample in this study was all 95 employees from various divisions at PT X. Sampling was carried out offline at PT X. The results of the study show that Leadership Style, Work Motivation, and Career Development have a negative and significant effect on Turnover Intention. The results of this study indicate that companies need to pay serious attention to the leadership practices implemented by managers or supervisors. An effective, communicative, and supportive leadership style can create a conducive work environment and increase employee engagement with the organization. Therefore, the management of PT X needs to develop a leadership training program that focuses on improving communication skills, employee empowerment, and team-oriented leadership. The results of this study contribute to the growing literature on turnover intention by confirming that a holistic approach, including leadership, psychological (motivational), and structural (career development) aspects, is more effective in explaining employee turnover intention than examining only one factor in isolation.